2015
DOI: 10.1371/journal.pone.0140771
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting Optimal Outcomes in Cognitive Therapy or Interpersonal Psychotherapy for Depressed Individuals Using the Personalized Advantage Index Approach

Abstract: IntroductionAlthough psychotherapies for depression produce equivalent outcomes, individual patients respond differently to different therapies. Predictors of outcome have been identified in the context of randomized trials, but this information has not been used to predict which treatment works best for the depressed individual. In this paper, we aim to replicate a recently developed treatment selection method, using data from an RCT comparing the effects of cognitive therapy (CT) and interpersonal psychother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
150
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 36 publications
9
150
1
6
Order By: Relevance
“…35 On the other hand, an even more recent trial from the Netherlands found no differences between IPT and CBT 36 with indications of differential response (moderation) on the part of different patients. 37 At this time it seems fair to say that IPT remains one of the best established treatments for depression although it is still not widely practiced outside of certain areas.…”
Section: Mindfulness-based Cognitive Therapy (Mbct)mentioning
confidence: 99%
“…35 On the other hand, an even more recent trial from the Netherlands found no differences between IPT and CBT 36 with indications of differential response (moderation) on the part of different patients. 37 At this time it seems fair to say that IPT remains one of the best established treatments for depression although it is still not widely practiced outside of certain areas.…”
Section: Mindfulness-based Cognitive Therapy (Mbct)mentioning
confidence: 99%
“…Optimal versus non-optimal treatment yielded a mean difference in depressive symptoms of 0.58 SD . Similarly, Huibers et al (2015) applied the personalized advantage index to inform selection of acute-phase CT versus interpersonal psychotherapy for MDD, focusing on post-treatment symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to investigate the preceding issue by employing a factor analysis of a personality disorder assessment interview within a depressed sample, thereby providing results relevant to both depression and personality disorder research. Particularly, understanding the factor structure of personality disorders and that a depressed individual’s score can vary on a particular factor or pattern of factors may play a substantial role in the process of personalizing a depressed individual’s specific treatment (e.g., see [9]).…”
Section: Introductionmentioning
confidence: 99%